2016
DOI: 10.1136/neurintsurg-2016-012494
|View full text |Cite
|
Sign up to set email alerts
|

Admission CT perfusion may overestimate initial infarct core: the ghost infarct core concept

Abstract: CT perfusion may overestimate final infarct core, especially in the early time window. Selecting patients for reperfusion therapies based on the CTP mismatch concept may deny treatment to patients who might still benefit from reperfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
161
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 149 publications
(169 citation statements)
references
References 23 publications
6
161
1
1
Order By: Relevance
“…In this study, we found a cutoff of approximately 4.5 h to imaging and of 5 h to recanalization as independent predictors of GIC in CBF < 30%. These results are in line with our previous findings [15] and others [9].…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…In this study, we found a cutoff of approximately 4.5 h to imaging and of 5 h to recanalization as independent predictors of GIC in CBF < 30%. These results are in line with our previous findings [15] and others [9].…”
Section: Discussionsupporting
confidence: 83%
“…GIC is defined as the infarct core initially predicted by CTP that appears as intact brain tissue on follow-up imaging. The existence of GIC implies that the initial core estimated by CTP may include, to some extent, salvageable brain tissue [15]. Characterization of this phenomenon is crucial to avoid exclusion of patients from a treatment that can still be of benefit.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations